(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article examines the impact of digitalization on the quality of life of the older generation in modern society of Uzbekistan from the point of view of subjective and objective approaches. Based on the analysis of domestic research data and the global trend of population aging, the main barriers to the involvement of older people in the digital space are identified. This is an objective challenge for the older generation to adapt to rapidly changing material and technical living conditions.